2020
DOI: 10.3390/cells9020399
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Associated Germinal Structures in Spermatogenesis: piRNA Pathway Regulation and Beyond

Abstract: Multiple specific granular structures are present in the cytoplasm of germ cells, termed nuage, which are electron-dense, non-membranous, close to mitochondria and/or nuclei, variant size yielding to different compartments harboring different components, including intermitochondrial cement (IMC), piP-body, and chromatoid body (CB). Since mitochondria exhibit different morphology and topographical arrangements to accommodate specific needs during spermatogenesis, the distribution of mitochondria-associated nuag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 114 publications
(230 reference statements)
2
33
0
Order By: Relevance
“…Fast metabolic changes in the germline are enabled by translational regulation [ 246 , 247 ]. This is most likely coordinated by the germ cell specific nuage, a ribonucleoprotein dense structure found in the cytoplasm [ 248 , 249 , 250 , 251 ]. This translational control allows for fast and efficient changes during spermatogenesis and can make transcriptional analysis misleading with regard to metabolic flux events.…”
Section: Metabolism Of Male Germ Cellsmentioning
confidence: 99%
“…Fast metabolic changes in the germline are enabled by translational regulation [ 246 , 247 ]. This is most likely coordinated by the germ cell specific nuage, a ribonucleoprotein dense structure found in the cytoplasm [ 248 , 249 , 250 , 251 ]. This translational control allows for fast and efficient changes during spermatogenesis and can make transcriptional analysis misleading with regard to metabolic flux events.…”
Section: Metabolism Of Male Germ Cellsmentioning
confidence: 99%
“…Our data suggest that mitochondria are an important vector of transport for the PEI granules, even though we cannot exclude a function for FB-MOs in this process. Interestingly, association of RNAi-related pathways with mitochondria has been described in various animals and include spermatogenic structures like pibodies, piP-bodies, chromatoid bodies and mitochondria-associated ER membranes (Wang et al, 2020). It appears that interaction with mitochondria may be used for various purposes in the context of small RNA pathways, ranging from small RNA biogenesis (Ge et al, 2019;Munafò et al, 2019) to the here identified role in transport and TEI.…”
Section: Transport Of Pei Granulesmentioning
confidence: 99%
“…The piRNAs are a kind of small non-coding RNA of 24-32 nucleotides in length, named this way because of their interactions with the PIWI subfamily of Argonaut proteins which exerts a transposon gene silencing effect besides other kinds of regulation such as epigenetics, gene and protein regulation, genome rearrangement, spermatogenesis, and germ stem cells maintenance (35)(36)(37). The piRNAs can be mainly involved in epigenetic regulation rather than post-transcriptional regulation of many biological phenomena such as cancer (38,39).…”
Section: Introduction Cancer Basics and Available Treatments Why Usementioning
confidence: 99%